2022
DOI: 10.1007/s11150-022-09606-w
|View full text |Cite
|
Sign up to set email alerts
|

Child development and distance learning in the age of COVID-19

Abstract: School closures, forcibly brought about by the COVID-19 crisis in many countries, have impacted children’s lives and their learning processes. The heterogeneous implementation of distance learning solutions is likely to bring a substantial increase in education inequality, with long term consequences. The present study uses data from a survey collected during Spring 2020 lockdown in France and Italy to analyze parents’ evaluations of their children’s home schooling process and emotional well-being at time of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 40 publications
0
6
1
Order By: Relevance
“…Surprisingly, we found that children in lower grades had more favorable attitudes toward remote learning compared to older students. This finding somewhat contradicts other studies reporting greater difficulties with remote learning among younger children [ 14 , 31 ].…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…Surprisingly, we found that children in lower grades had more favorable attitudes toward remote learning compared to older students. This finding somewhat contradicts other studies reporting greater difficulties with remote learning among younger children [ 14 , 31 ].…”
Section: Discussioncontrasting
confidence: 99%
“…Socioeconomic Background: Students from higher socioeconomic status (SES) backgrounds are more likely to have acquired the necessary critical thinking skills associated with selectively accessing and assessing technology content, as well as having the financial means to gain help [ 13 , 14 , 15 ]. Moreover, studies indicated that financially disadvantaged groups were less likely to engage in remote learning, and thus students from low-income families naturally struggled more with the sudden shift to remote learning [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The COVID-19 pandemic and the related policies to stop the spread of the coronavirus, particularly school closures, present a severe shock to mental and physical well-being for millions of young individuals worldwide. Distancing measures may affect the mental and physical health and life satisfaction of young individuals, as these measures massively change the schooling, learning processes and leisure activities of students, such as physical activity, time spent in front of screens, social contacts, substance use, and sleep time (Belot et al, 2021 ; Champeaux et al, 2020 ; Davis, 2021 ; Hisler & Twenge, 2021 ; Orgilés et al, 2020 ; Shanahan et al, 2020 ). Families with younger kids suffered from decreased well-being (Pisano et al, 2020 ; Stassart et al, 2021 ) but pandemic policies may especially impact the well-being of young individuals who are close to graduation because the measures not only affected schooling and leisure but also strongly reduced students’ perceived career security and job and educational opportunities.…”
Section: Motivationmentioning
confidence: 99%